Early auditory skills development in Mandarin speaking children after bilateral cochlear implantation. (November 2018) - Long, Yue; Liu, Haihong; Li, Ying; Jin, Xin; Zhou, Yi; Li, Jing; Zheng, Zhipeng; Liu, Peng; Zhao, Yawen; Zheng, Jun; Zhang, Jie; Chen, Min; et al.
Abstract: Objectives: The purpose of the present study was: (1) to investigate the early auditory preverbal behaviors of infants/toddlers with bilateral cochlear implants (BCI), and to compare their performance with that of unilateral cochlear implant (UCI) peers; (2) to investigate effects of age of implantation, education level of caregivers, living environment, and unaided behavioral threshold before operation on early auditory preverbal development. Methods: The evaluation material of the present study was the Mandarin version of the LittlEARS ® Auditory Questionnaire (LEAQ). Assessments were administrated at 0, 1, 2, 3, 6, 9, 12 and 24 months after cochlear implants (CIs) were switched on. A one-way ANOVA was used to analyze the differences of early auditory preverbal performance between each two contiguous test intervals. A two-sample t -test was used to analyze the difference of behaviors between infants/toddlers with BCI and UCI. Non-parametric tests were used to analyze the effects of potential affecting factors on auditory preverbal skills. Results: Nineteen subjects aging from 9 to 54 months (Mean = 22.7, SD = 13.7) were recruited in the study. At each evaluation time, the average scores of LEAQ were 4.58, 9.00, 16.00, 18.56, 22.00, 31.50, 29.67, and 34.35 respectively. The total score and semantic auditory behavior score increased significantly during the second months after CIs activation (the total score: LSD-t = 3.157, p = 0.030; semantic auditory behavior score: LSD-t = 1.972, p = 0.034). The score of BCI group was significantly higher than UCI group after 1, 3 and 6 months of CI use (1 month: t = 3.257, p = 0.002; 3 months: t = 5.042, p = 0.000; 6 months: t = 4.054, p = 0.000). Education level of caregivers had a positive effect on receptive auditory behavior (H = 6.538, p = 0.035) after CIs switched on for 3 months. The LEAQ performance was not significantly correlated with pre-operative behavioral threshold although they showed a trend of negative correlation in the first 3 months after activation. Conclusion: The study indicated that infants and toddlers who underwent BCI had better auditory preverbal skills than their UCI peers. Higher caregivers' education level positively correlated with the early development of auditory preverbal skills. Better pre-operative behavioral threshold might also benefit early auditory preverbal skills development for BCI children.